Conditions for the approximated analytical solution of a parametric oscillation problem described by the mathieu equation - Bich, Nguyen Dang; Nam, Ngo Dinh Bao (VNU Journal of Science: Mathematics - Physics; Vol 22 No 2, 2006)
Abstract